Tinjauan Maqoshid Syariah pada Marketplace Otomotif (Studi Komparatif pada OLX dan OtoDeals) - Saijun; Syahril Ahmad; Victor Diwantara; Agusriandi (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2022)
This research aims to review the practice of buying and selling in automotive marketplaces in Indonesia based on the maqoshid sharia aspect. The marketplace cases are taken from OLX and OtoDeals. Content analysis on the marketplace is used to describe the object of research, while the normative descriptive method is used to review the maqoshid sharia aspects. The results of the study show that in general the two marketplaces already support the maqoshid sharia aspect, but there are still aspects such as hifzul maal such as the certainty of the originality of goods and using riab as payment term